Autoadjusting Positive Pressure Trial in Adults with Sleep Apnea Assessed by a Simplified Diagnostic Approach - Torre-Bouscoulet, Luis (American Academy of Sleep Medicine, 2008)
STUDY OBJECTIVES: To describe our clinical experience with autoadjusting positive airway pressure (APAP) trials carried out on patients with moderate-to-severe obstructive sleep apnea (OSA). METHODS: Consecutive CPAP-naïve adults underwent a non-attended home APAP trial (ResMed, Autoset, Spirit). Diagnoses of OSA were established by simplified polygraphy. RESULTS: Data from 208 men and 71 women. The median age (interquartile range) was 51 years (41–59), with an Epworth Sleepiness Scale score of 13.5 (9–19), body mass index of 33 kg/m(2) (29–38) and respiratory disturbance index (RDI) of 53 events/h (35–74). The APAP trial results included: hours used per night, 5.5 (4–7); 95(th) percentile pressure, 10.6 cm H(2)O (9.4–11.7); 95(th) percentile leak, 0.3 L/sec (0.1–0.6); residual RDI, 6.2 events/h (3.9–11.4); and percentage change in RDI, 87% (74–93). The proportion of patients with residual RDI >10 events/h was 29% (95% CI 23.6–34.3). Adherence (≥70% of nights and ≥4 h/night) was observed in 72.4% of subjects (95% CI 67–78). Patients with APAP adherence tended to require higher CPAP pressures, had higher rates of residual RDI, and had a lower percentage change in RDI than those with no adherence. As the 95(th) percentile CPAP pressure increased so too did residual RDI. CONCLUSIONS: The APAP trial was effective in decreasing RDI with an acceptable adherence rate; however, residual OSA was a frequent finding. Our results support that in up to one-third of patients evaluated by a simplified diagnostic approach, CPAP titration based on 95(th) percentile pressure may not be sufficient if residual RDI <10 events/h is considered as a therapeutic target. CITATION: Torre-Bouscoulet L; Meza-Vargas MS; Castorena-Maldonado A; Reyes-Zúñiga M; Pérez-Padilla R. Autoadjusting positive pressure trial in adults with sleep apnea assessed by a simplified diagnostic approach. J Clin Sleep Med 2008;4(4):341–347.